الاصولية والمحافظون الجدد في توجيه السياسة الخارجية الامريكية: دراسة تحليلية (Journal of Academic Research, 2025)
Abstract:This analytical study explores the complex ideological intersection between religious fundamentalism-particularly evangelical Protestantism-and the neoconservative movement in shaping the trajectory of American foreign policy. The central thesis is that the alliance between these two powerful forces reoriented the strategic priorities of the United States, especially following the transformative events of September 11, 2001. The study begins by tracing the historical roots of American religious fundamentalism, emphasizing the theological and cultural heritage brought by early Puritan settlers. These settlers envisioned America as a "New Israel" and believed in their divine mission to shape global morality. Over time, these beliefs evolved into a structured political force, especially within evangelical churches that began exerting influence over American political life. On the other hand, the rise of the neoconservatives-a group of intellectuals, many from liberal or leftist origins, who later shifted to the political right-is examined in detail. They emerged as a strong political bloc in the latter half of the 20th century, advocating for American global dominance through preemptive military power and moral interventionism. The convergence of these two camps became most evident during the administrations of Ronald Reagan and George W. Bush, with the latter witnessing the full mobilization of this ideological alliance in the post-9/11 world. The study illustrates how neoconservative strategists such as Paul Wolfowitz and Dick Cheney, Page 1 along with evangelical influencers, promoted a foreign policy rooted in binary narratives of good versus evil, often reinforced by apocalyptic Christian visions like Armageddon. This fusion provided a religious justification for aggressive U.S. interventions, particularly in the Middle East, and established unwavering support for Israel as part of a divine prophecy. Ultimately, the study concludes that American foreign policy has, at key moments, transcended conventional realism or pragmatism, becoming a vehicle for ideological and theological objectives. This has profound implications for international relations, as decisions of global consequence are often shaped by deeply held religious convictions rather than purely rational state interests. Understanding this religious-political nexus is essential for decoding America's global behavior and for anticipating the moral and strategic narratives that shape its actions on the world stage